2016
DOI: 10.1007/s11121-016-0715-7
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Coping Power Adapted as a Universal Prevention Program in Italian Primary Schools: a Randomized Control Trial

Abstract: Behavioral problems in schools can cause serious harm to the emotional and social well-being of students and limit their ability to achieve their full academic potential. A prior pilot study on the universal application of Coping Power showed a significant decrease in the hyperactivity behaviors of five classes. The next step was to test whether Coping Power Universal could be successfully implemented by teachers in a variety of Italian schools. The sample involved 40 third- and fourth-grade classes (901 stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…Considering our experience, we can suggest that it is possible to adapt some aspects of evidence-based curricula to the national culture. Importantly, these adaptations must be related to the principles of the original model, if not, the adaptations would change the very nature of the intervention (Muratori et al., 2017b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering our experience, we can suggest that it is possible to adapt some aspects of evidence-based curricula to the national culture. Importantly, these adaptations must be related to the principles of the original model, if not, the adaptations would change the very nature of the intervention (Muratori et al., 2017b).…”
Section: Discussionmentioning
confidence: 99%
“…Two previous studies indicated that the CPU could reduce behavioral problems in primary school classes (Muratori et al., 2015, 2017b). Although previous evidence showed positive results for the CPU in elementary school, it could be important to intervene earlier.…”
Section: The Coping Power Universalmentioning
confidence: 99%
“…The CPU intervention manual describes each lesson, though teachers were free to adapt the activities to the characteristics of their students. A more detailed description of the CPU activities is reported in previous studies, see for instance [4,8].…”
Section: Interventionmentioning
confidence: 99%
“…A wealth of studies has recognized the CPU's positive effects, including reducing behavioral problems, improving prosocial behavior, and academic skills [4][5][6][7][8], to the point that it was included in the Blueprints for Healthy Youth Development's list of certified promising programs. However, to date, only a study has tested whether the positive effects of the CPU are maintained in the long term [8]. Despite the promising results of this previous work, more studies investigating whether the CPU can yield long-lasting effects are needed.…”
Section: Introductionmentioning
confidence: 99%
“…However, a lag time of a few years is typical of meta-analysis, given the amount of time it takes to survey and collect the existing research studies, do the analyses, conduct the peer review process, and go through the usual publication timeline. It is worth noting, though, that individual studies appearing up through at least the fall of 2017 have continued to report positive effects for SEL (e.g., Duncan et al, 2017;Miller et al, 2017;Muratori et al, 2017).…”
Section: Comparison Of Follow-up Outcomes For Two Meta-analyses Of Sementioning
confidence: 99%